2022
DOI: 10.1136/bmjresp-2022-001210
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and their caregivers’ experiences with regular, low-dose, sustained-release morphine for chronic breathlessness associated with COPD: a qualitative study

Abstract: IntroductionRegular, low-dose, sustained-release morphine is effective in reducing chronic breathlessness in people with advanced disease, particularly in patients with chronic obstructive pulmonary disease (COPD). Despite experiencing a reduction in breathlessness, some patients choose not to continue long-term treatment.AimThis study aimed to explore patients’ and caregivers’ experiences with regular, low-dose, sustained-release morphine for chronic breathlessness associated with COPD.MethodsA qualitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Results suggest functional improvement is a key driver of perceived benefit, which seems to be accompanied by clinically meaningful reductions in CRQ-dyspnoea [6], appreciable improvements in mMRC scores and an increase in active steps/day. Compared to participants reporting small or no benefit, super-responders reported that they could do more meaningful activities [5]. More importantly, they actually engaged in such activities, which is not always the case for people who increase their functional capacity [7].…”
Section: Now I Can Walk Down To the Letter Box With No Problem It Has...mentioning
confidence: 98%
See 4 more Smart Citations
“…Results suggest functional improvement is a key driver of perceived benefit, which seems to be accompanied by clinically meaningful reductions in CRQ-dyspnoea [6], appreciable improvements in mMRC scores and an increase in active steps/day. Compared to participants reporting small or no benefit, super-responders reported that they could do more meaningful activities [5]. More importantly, they actually engaged in such activities, which is not always the case for people who increase their functional capacity [7].…”
Section: Now I Can Walk Down To the Letter Box With No Problem It Has...mentioning
confidence: 98%
“…There was an optional 6-month blinded extension using the dose prescribed in week 3. 13 patients and, separately, their caregivers were interviewed about their experiences of persistent breathlessness before and after initiating the study medication as part of a pre-planned qualitative study [ 5 ]. Interviews were conducted at participants’ homes, while the participants and interviewer were still blinded.…”
mentioning
confidence: 99%
See 3 more Smart Citations